The Incidence of Laryngotracheal Stenosis in Neonates With a History of Ventilator‐Associated Pneumonia. (4th December 2019) - Lowery, Anne Sun; Gelbard, Alexander; Wootten, Christopher
Abstract : Objectives/Hypothesis: Neonatal patients requiring prolonged intubation are susceptible to both infection and laryngotracheal stenosis (LTS). This study investigated the effect of ventilator‐associated pneumonia (VAP) on the development of LTS in neonates. Study Design: Retrospective case–control study. Methods: The incidence of LTS in neonates with VAP was compared with the incidence of LTS in matched intubated controls without VAP. Patients were treated at a tertiary‐care medical center from 2004 to 2014. Eligible patient records were assessed for the development of LTS. Demographics, medical comorbidities, infection characteristics, and treatment variables were compared using unpaired t test or χ 2 test. Statistical significance was set a priori at P  < .05. Results: When comparing the VAP patients with matched non‐VAP controls, we found no significant differences in the incidence of LTS (VAP vs. non‐VAP, 8.3% vs. 6.7%; P = .73). In subgroup analysis of the VAP cohort, LTS and non‐LTS patients demonstrated similar VAP organisms on broncho‐alveolar lavage ( Klebsiella pneumoniae, Pseudomonas aeroginosa, Escherichia coli, methicillin‐resistant Staphylococcus aureus, Streptococcus pneumoniae, and Enterobacter ). Additionally, within the VAP cohort, LTS and non‐LTS patients showed similar gestational age (LTS vs. non‐LTS, 31.3 days vs. 28.1 days; P = .22), birth weight (LTS vs. non‐LTS, 1.6 kg vs. 1.2 kg; P = .33), and similar intubation duration (LTS vs. non‐LTS, 37.8 days vs. 27.5 days; P = .52). Conclusions: In this neonatal cohort, VAP was not associated with an increased incidence of LTS. Given severity of the burden of LTS on the healthcare system, multi‐institutional longitudinal investigation into contributing risk factors for neonatal LTS is warranted. Level of Evidence: NA Laryngoscope, 130:2252–2255, 2020